(untitled) (Vietnam Journal of Community Medicine, 2026)
Research results show the presence of both Aedes mosquito species in Quang Ninh, in which the proportion of Ae. albopictus is 82.2%, much higher than that of Ae. aegypti is 17.8%. Mosquito Ae. aegypti 100% were found in the house with 35 individuals. Mosquito Ae. The rate of Albopictus found indoors was 49 individuals, equivalent to 30.2%, while the rate of finding Ae. Albopictus outside the house is 113 individuals, equivalent to 69.8%. The density distribution of mosquitoes and larvae of the two Aedes mosquito species is different. Larvae and mosquito densities are present in the months from April to November. August-October is the time when the index of Aedes species is highest (BI = 57, MDM = 0.5 fish/house). Water containers with Aedes larvae in jars, jars, buckets, barrels, waste, flower vases, ornaments, and coffee pots, of which the water containers with the most Aedes larvae are buckets and barrels, accounting for 31.3% (87 DCCN) and waste 26.6% (74 DCCN. It is necessary to monitor, supervise and evaluate the dengue vector index in the peak months of April - November, especially the months of August - October. Effective work The most important way to prevent the disease is to destroy larvae nests, and at the same time, it is necessary to propagate and raise people’s awareness about dengue prevention measures